2011
DOI: 10.1258/ebm.2011.010399
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum supplementation improved high-fat-fed-induced metabolic syndrome and promoted intestinal Reg I gene expression

Abstract: Recent evidence suggests that intestinal Bifidobacterium species (spp.) positively correlates with improved insulin resistance and obesity, and this might be linked to metabolic inflammation. The expression of intestinal REG (regenerating) family proteins which are widely involved in inflammatory bowel disease and diabetes are still unknown in metabolic syndrome. Hence, we investigated the effects of Bifidobacterium longum (BIF) supplementation on metabolic parameters, intestinal function and expression of Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 60 publications
(56 reference statements)
4
67
2
1
Order By: Relevance
“…Several reports have demonstrated the importance of selected bacteria [i.e., Lactobacillus spp (30, 31), Bifidobacterium spp (32,33), and Bacteroides uniformis CECTT 7771 (34)] on fat mass development during diet-induced obesity, but the aims of these studies were different from that of the present study. These studies investigated the impact of supplementation with one specific probiotic strain or strains that were isolated from healthy infants on physiological parameters.…”
Section: Discussionmentioning
confidence: 64%
“…Several reports have demonstrated the importance of selected bacteria [i.e., Lactobacillus spp (30, 31), Bifidobacterium spp (32,33), and Bacteroides uniformis CECTT 7771 (34)] on fat mass development during diet-induced obesity, but the aims of these studies were different from that of the present study. These studies investigated the impact of supplementation with one specific probiotic strain or strains that were isolated from healthy infants on physiological parameters.…”
Section: Discussionmentioning
confidence: 64%
“…Multiple in-vivo studies provide evidence that some probiotics can reduce diet-induced obesity in rodents [11][12][13][14][15][16][17][18], although there are reports of probiotics with no effect on body weight gain [19] or in some cases probiotics that actually cause weight-gain in rodents [20]. While many studies indicate probiotics intake causes functional changes, such as lower blood lipids in hyperlipidemic animals [21], evidence is lacking for the impact of probiotics containing individual or multiple bacterial species on gut microbiota diversity and composition of obese animals.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was demonstrated that feeding Bifidobacterium improved several aspects of the metabolic syndrome reducing endotoxin concentration and intestinal inflammation. 76,77 However, these effects seem to be strain-dependent, which requires a detailed understanding of each strain and the way it affects fat and glucose metabolism. 78 As concerns Lactobacillus supplementation, although there is experimental data showing its effects in reduction of body weight, 79,80 some studies do not report these differences.…”
Section: Probioticsmentioning
confidence: 99%